Multimedia supported study of achieving high worker's efficiency in relation to his work - Balantič, Zvone (Informatica (Ljubljana), 2001)
Electronics, engineering and medicine expert collaboration as rule requires knowledge of both the remaining fields from each of experts to result in a useful application. Ergonomics and work process management are the goals achieved by such approach. Comprehensive analysis of work process, influences by environmental factors and output, measured as a function of these influences, is a cornerstone of these multimedia CD compilation, presented both in a textbook and handboook format. In the electronic publication study contents are combined with practical experience of different Slovenian companies, which were prepare to present a piece of their experinece.
Keywords: elektronske publikacije; multimedia; education; izobraževanje; ergonomija